Spanish word generation dataset from structured consonant prompts - Jon Andoni Duñabeitia (Scientific Data)
Abstract This dataset captures responses from a lexical generation task designed to examine word production under structural constraints. Native Spanish speakers were presented with three-consonant strings and instructed to generate valid five-to-seven-letter Spanish words by inserting only vowels, maintaining the consonants in their original relative order. The task was conducted under time pressure and without semantic cues, allowing researchers to explore lexical access, phonotactic preferences, and the role of consonants and vowels in word formation processes. The dataset includes both item-level and participant-level files. Item-level data comprise individual responses with lexical frequency, word length, and response time. Participant-level data summarize age, gender, and aggregate lexical metrics per individual. This resource enables a range of investigations, including analyses of syllabic structures, relative consonant positioning, lexical diversity, and frequency effects. The dataset is encoded in UTF-8 CSV format and is directly compatible with standard data analysis environments. It offers a valuable tool for researchers studying lexical creativity and orthographic processing in Spanish.